MORPHOLOGICAL CHARACTERISTICS AND BIOECOLOGICAL PECULIARITIES OF DEVELOPMENT OF TUTA ABSOLUTA POVOLNY (LEPEDOPTERA:GELECHIIDAE) UNDER LABORATORY CONDITIONS - Alimbekova Ainur Kabylova; Duisembekov Bakhytzhan Alisherovich; Khidirov Kenzheali Rahimovish; Chadinova Aizhan Mukasheva; Zhumadulaeva Alisa Isaevna (Academic Journal of Physical and Chemical Sciences, 2021)
. The article provides data on the determination of morphological features and bioecological features of the development of a particularly dangerous object Tuta absoluta (Povlony) in laboratory and greenhouse conditions. In greenhouses and laboratory conditions, the imago begins to actively mate 3-4 hours before sunrise. In laboratory conditions, females lay eggs on the surface of leaves (35%), below (45%), stems (15%), fruit leaves (5%), but the fruit was not laid. After hatching from the eggs, the larvae chew through the entrance to the mesoderm of the leaf and penetrate for 5 minutes. The Larva Of T. absoluta is almost cylindrical in shape, with a distinct head, three pairs of pectoral legs, and five pairs of ventral pseudopods. After completing all five stages of development, the larvae emerge from the mine, and sometimes pupate there. Before pupation, the larva changes its color from dark green to light green. The pupa of the tomato moth, as in other Lepidoptera, is of the “obtecto " type, that is, with the future appendages of adults. It has the shape of a cone 4.5-5 mm long and 1.3-1.5 mm wide, greenish in color, turning to a more intense brown, and at the end of development becomes brown. In the population, females predominate over males. At a temperature of 15°C and 33°C the ratio of female to female life expectancy varies. The higher the air temperature, the more females predominate in the population.